Reestructuración técnico administrativa de la empresa Industrias Salper LTDA. Ubicada en Bogotá D.C. (2017)
The technical and administrative restructuring of the company Industrias Salper Ltda., Located in Bogotá D.C; A diagnosis was made to know the current situation; Where tools such as business self-diagnosis were used to determine the internal panorama; A PESTEL analysis was developed to know the external factors and then synthesized this information in the SWOT matrix, where it was evidenced that the company presents opportunities for growth in the market. In the technical study the selection of the two products was made through the working methods, it was determined that for the two products there was a reduction of 42.73 minutes. Finally, in the administrative study, a strategic planning, an organizational structure was proposed and a financial analysis was carried out, obtaining a present value (NPV) of $ 39,135,326 COP and an internal rate of return (IRR) of 25% Therefore the project is considered viable.